The intersection of fashion and theater in the reuse of jeans to create a costume (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article analyzes the process of creating and executing costumes for an academic theater production at the School of Theater and Cinema of the Polytechnic Institute of Lisbon in 2024. It uses observation during rehearsals, conversations between the director and the visual arts team, notes, and some of the stages of costume design. It offers a case study of the process of creating a stage costume using denim as the raw material, with references to fashion and sustainability in mind.